HUMAN RESOURCE MANAGEMENT'S FUNCTION IN THE DEVELOPMENT OF LEADERSHIP - Masharipova Sabina Azamat qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The article's goal is to illustrate the contribution human resources (HR) may make to managers' and leaders' efficacy.